MiR-199b-5p Promotes Gastric Cancer Progression by Regulating HHIP Expression - Chen, Songda; Wu, Huijie; Zhu, Lingyu; Jiang, Mengjie; Wei, Shuli; Luo, Jinhua; Liu, Aiqun (Frontiers in Oncology, 2021)
Objectives: Gastric cancer (GC) is one of the most common malignant tumors. More and more evidences support the role of microRNAs (miRNAs) in tumor progression. However, the role of miRNAs in human GC remains largely unknown. Methods: Based on the published GC expression profile data, combined with bioinformatics analysis, potential miRNAs in the process of GC were screened. The expression of miR-199b-5p in GC cells and patients' plasma was detected by RT-PCR. The effects of miR-199b-5p on GC in vitro were detected by EdU proliferation assay, colony formation assay, Transwell assay and wound healing assay. Western blot was used to detect EMT related proteins. The subcutaneous tumorigenesis model and metastatic tumor model of mice were used to study its effect in vivo. Dual luciferase reporter assay were used to verify the effect of miR-199b-5p and its target gene. Results: we screened a novel miRNA miR-199b-5p that was significantly up-regulated in GC tissue and associated with poor prognosis of GC patients. RT-PCR results showed that its expression was also up-regulated in GC cell lines and patients' plasma. MiR-199b-5p can significantly promote GC cell proliferation and migration in vitro and in vivo. Western blot showed that miR-199b-5p could promote the EMT process of GC. HHIP has been proved to be a target of miR-199b-5p, and the recovery of HHIP can weaken the effect of miR-199b-5p. Conclusion: MiR-199b-5p may play an oncogene role in GC by targeting HHIP, suggesting that miR-199b-5p may be a potential therapeutic target for GC.